2017
DOI: 10.1088/1361-6501/aa53a8
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford Probe: an open access five-hole probe for aerodynamic measurements

Abstract: The Oxford Probe is an open access five-hole probe designed for experimental aerodynamic measurements. The open access probe can be manufactured by the end user via additive manufacturing (metal or plastic). The probe geometry, drawings, calibration maps, and software are available under a creative commons license. The purpose is to widen access to aerodynamic measurement techniques in education and research environments. There are many situations in which the open access probe will allow results of comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
4
25
0
Order By: Relevance
“…During the development of the Oxford Probe, it was observed that the Reynolds number sensitivity of the calibration map was small for Re D > Re D,crit = 1.5 × 10 4 [7]. This Reynolds sensitivity threshold is in accordance with previous research (e.g.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…During the development of the Oxford Probe, it was observed that the Reynolds number sensitivity of the calibration map was small for Re D > Re D,crit = 1.5 × 10 4 [7]. This Reynolds sensitivity threshold is in accordance with previous research (e.g.…”
Section: Introductionsupporting
confidence: 91%
“…Perhaps the most common type, in applications where the entire flow structure is to be assessed, is the five-hole probe, which is widely used in turbomachinery surveying applications. Turbomachinery flows are generally characterized by Reynolds numbers in the range 10 5 < Re L < 10 7 , where we set L to an arbitrary value of order 50 mm, which is of the order of the chord length of a nozzle guide vane or rotor blade [2,3]. This represents a Mach number range of 0.3 < M < 1.3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-hole probe was calibrated over a Mach number range of 0.3-0.7 and a yaw angle range of ±40 deg using the Oxford Probe Calibration Facility, described in Ref. [15]. The frequency responses of the three-hole probe and thermocouple probes measurements were independently estimated to be approximately 100 Hz, based on experimentally validated analytical predictions described in Refs.…”
Section: Coolant Supply and Mass Flowmentioning
confidence: 99%
“…Cone tips, on the other hand, are generally fully calibrated in the wind tunnel and the cone angle allows for an adjustment of the angle-sensitivity of the measurement. An overview of relevant geometries and aerodynamic probe design, can be found e.g., in the study of Hall and Povey [38]. MASC uses a five-hole probe ( Figure 2) with a tip diameter of 4 mm, a cone angle of φ = 60 • , forward facing holes and is calibrated from −20 • to 20 • .…”
Section: Five-hole Probe "Pressures-to-airflow-vector"mentioning
confidence: 99%